ANALYSIS OF THE INFLUENCE OF HUMAN RELATIONSHIP, TRANSFORMATIONAL LEADERSHIP STYLE, AND MOTIVATION ON THE PERFORMANCE OF TAYU AMANAH KSPPS EMPLOYEES BERKAH ADI PATI - Arini Novandalina; Fidyah Yuli Ernawarti; Evinta Amalia Amalia Nurhidayah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Employee performance is an important thing to pay attention to, because at the organizational level, performance targets can affect the achievement of targets that have been set. Performance measurement is the process by which the organization determines the outcome parameters to be achieved by the programs, investments and acquisitions made. This research is a quantitative study with a population of 90 KSPPS Tayu Amanah Berkah Adil Pati employees. The sampling technique in this study was carried out randomly so that the number of samples taken was 47 people. The method of data analysis in this study uses the classical assumption test, multiple linear analysis, and hypothesis testing. The results showed that human relationships did not have a significant effect on employee performance, while transformational leadership style and motivation had a significant positive effect on employee performance. It was suggested that the management team of the Tayu Amanah Berkah Adil Pati KSPPS need to improve how interactions between one person and another person can be created. a comfortable and transparent working atmosphere, thereby affecting the quality of employee performance.